Update on Treatment of Infantile Hemangiomas: What’s New in the Last Five Years? - Macca, Laura; Altavilla, Domenica; Di Bartolomeo, Luca; Irrera, Natasha; Borgia, Francesco; Li Pomi, Federica; Vaccaro, Federico; Squadrito, Violetta; Squadrito, Francesco; Vaccaro, Mario (Frontiers in Pharmacology, 2022)
Among benign vascular tumors of infancy, haemangiomas are the commonest, affecting approximately 5 to 10 % of one-year-old children. They are derived from a benign proliferation of vascular endothelial cells (VECs) in the mesoderm and may arise anywhere on the body around 1-2 weeks after birth. Infantile haemangiomas (IHs) are characterized by an early proliferative phase in the first year followed by a spontaneous progressive regression within the following 5 years or longer. IH prevalence is estimated to be 5 to 10% in one-year-old children and commonly affects female, Caucasian and low-birth weight infants. Although most of them spontaneously regress, approximately 10% requires treatment to prevent complications due to the site of occurrence such as bleeding, ulceration, cosmetically disfigurement, functional impairment, or life-threatening complications. For over 30 years, steroids have represented the first-line treatment for IHs, but recently topical or systemic β-blockers are increasingly being used and recognized as effective and safe. A search for “cutaneous infantile emangiomas treatment” was performed by using PubMed and EMBASE databases. Treatment of IHs with steroids and topical and systemic β-blockers, including topical and oral propranolol, topical timolol, topical carteolol, with a focus on formulations types and adverse events, and the experiences with other off-label drugs, such as itraconazole or sirolimus, were described in our review. We also discussed the benefits of pulsed dye laser and the treatment of IHs with involvement of central nervous system, namely the PHACE and LUMBAR syndrome.